2020
DOI: 10.1021/acs.cgd.0c00589
|View full text |Cite
|
Sign up to set email alerts
|

Metastable structures of CaCO3 and their role in transformation of calcite to aragonite and postaragonite

Abstract: Using molecular dynamics simulation and evolutionary metadynamic calculations, a series of structures were revealed that possessed enthalpies and Gibbs energies lower than those of aragonite but higher than those of calcite. The structures are polytypes of calcite, differing in the stacking sequence of closepacked (cp) Ca layers. The two-and six-layered polytypes have hexagonal symmetry P6 3 22 and were named hexarag and hexite, respectively. Hexarag is similar to aragonite, but with all the triangles placed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…Surprisingly, the computationally predicted CaCO 3 polymorph spontaneously generates at the (001) Ar /(00.1) Cc interface and at low temperature (0 K), is the same as that already obtained by other researchers, when studying the high-temperature aragonite–calcite breakdown by means of both empirical , and quantum-mechanical simulations . In particular, Gavryushkin et al, through molecular dynamics simulation at the quantum-mechanical level and evolutionary metadynamic calculations, found that the aragonite structure was stable up to 700–800 K. At 800 K, the new phase with hexagonal symmetry was formed and was stable up to 1000 K; this hexagonal CaCO 3 polymorph was named hexarag (hAr). Instead, at an empirical level, depending on the potential used the phase transition from aragonite to hexarag has been fixed at 500 and 1706 K, respectively.…”
Section: Resultssupporting
confidence: 83%
“…Surprisingly, the computationally predicted CaCO 3 polymorph spontaneously generates at the (001) Ar /(00.1) Cc interface and at low temperature (0 K), is the same as that already obtained by other researchers, when studying the high-temperature aragonite–calcite breakdown by means of both empirical , and quantum-mechanical simulations . In particular, Gavryushkin et al, through molecular dynamics simulation at the quantum-mechanical level and evolutionary metadynamic calculations, found that the aragonite structure was stable up to 700–800 K. At 800 K, the new phase with hexagonal symmetry was formed and was stable up to 1000 K; this hexagonal CaCO 3 polymorph was named hexarag (hAr). Instead, at an empirical level, depending on the potential used the phase transition from aragonite to hexarag has been fixed at 500 and 1706 K, respectively.…”
Section: Resultssupporting
confidence: 83%
“…On a pressure increase, calcite is known to transform into metastable high-pressure polymorphs (CaCO 3 -II, CaCO 3 -IIIb, CaCO 3 -III, and CaCO 3 -VI , ). CO 2 dry ice transforms into CO 2 -III at ∼11 GPa .…”
Section: Resultsmentioning
confidence: 99%
“…The simplification of the atomic nets in the crystal structures is actively used to classify various types of chemical compounds, both organic or metal-organic (O'Keeffe & Yaghi, 2012;Xie et al, 2019;Shevchenko et al, 2020), and inorganic (Kabanova et al, 2020;Gavryushkin et al, 2021). For example, the classification of zeolite frameworks (Baerlocher & McCusker, 2017) becomes more universal and comprehensive after applying the principles of topological classification based on underlying nets.…”
Section: Kinds Of Representations Of Atomic Netsmentioning
confidence: 99%